Pharmacists' roles in mental healthcare: Past, present and future - Sarira El-den; Jack C. Collins; Timothy F. Chen; Claire L. O'Reilly (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Mental illnesses cause significant disease burden globally, with medicines being a major modality of treatment for most mental illnesses. Pharmacists are accessible and trusted healthcare professionals who have an important role in supporting people living with mental illness. This commentary discusses the role of pharmacists in mental healthcare, as part of multidisciplinary teams, the current evidence to support these roles, and the training, remuneration and policy changes needed to recognize these roles and embed pharmacists as core members of the mental healthcare team.